Effectiveness of Contextual Guessing Strategy on Reading Comprehension in Indonesian EFL Pre-University Students: A Mixed-Methods Study - Nurul Hasanah; Syahban Mada Ali; Rahma Melati Amir (Universitas Muhammadiyah Barru, 2024)
This study examines the effectiveness of contextual guessing strategies in enhancing reading comprehension among Indonesian pre-university EFL students in Parepare. The research targeted students preparing for university entrance exams, employing a mixed-methods approach with a quantitative-driven design. A purposive sampling technique selected 30 pre-university students from various high schools in Parepare. Quantitative analysis of multiple-choice test scores before and after a targeted intervention, which trained students to use contextual clues (e.g., roots, prefixes, and suffixes) to infer meanings of unfamiliar words, demonstrated a significant improvement in reading comprehension (t(29) = 12.24, p < 0.05). Qualitative insights from interviews with these students revealed increased confidence, practical relevance, and engagement with texts. Students reported that these strategies helped them approach reading tasks analytically, manage their time effectively during exams, and reduce reliance on dictionaries. The findings underscore the critical role of contextual guessing strategies in EFL instruction, promoting effective reading skills and academic success for pre-university students in Indonesia. Integrating these strategies into the curriculum can substantially enhance reading comprehension and exam performance.